MULTIVARIATE ASSESSMENT OF THE IMPACT OF INVESTMENT ACTIVITY ACTIVITIES ON THE COST OF AN OIL COMPANY - A. Gvozdik; Y. Rudneva (Вестник Северо-Кавказского федерального университета, 2022)
The article proposes a methodology for the formation of a multifactor correlation and regression model for assessing the value of PJSC JSOC Bashneft, the application of which will have an impact on the company's capitalization when choosing an investment strategy. As a result of the analysis of the investment activities of PJSC ANK Bashneft and possible limiting factors, 3 investment strategies were drawn up: Conservative, Accelerated, and Spot, which take into account the company's ability to develop individual sectors. For each strategy, a forecast of the main financial and economic indicators. To assess the impact of the investment development option on the cost of PJSC JSOC Bashneft, linear and power-law correlation-regression models were formed that included 4 and 6 factors. The following factors are included in the model: revenue, value of non-current assets, equity, net profit, amount of dividends paid and oil price.